046: EVALUATION OF A RESEARCH CAPACITY-BUILDING PROGRAM FOR HEALTH SCIENCES STUDENTS IN A PHILIPPINE UNIVERSITY. (24th August 2015) - Wong, John Quan; Uy, Jhanna
Abstract : Background: A broad high-quality evidence base is necessary to improve health through universal health coverage. This is not possible without country capacity to conduct health systems research. A Health Sciences course in a Philippine university has been attempting help fill this gap through a research capacity building program for its undergraduates. Objectives: To evaluate the effectiveness of the health research capacity-building program for Health Sciences students. Methods: An evaluation framework for research capacity building in health care practices was adapted to the academic setting. The analysis was limited to student research teams and five variables: building skills and confidence, developing linkages and partnerships, developing appropriate dissemination, investments in infrastructure, and building elements of sustainability and continuity. Document review was conducted among submitted research papers. A survey was sent out to all graduates and a focus group discussion was conducted with a representative sample. Result: The program developed a basic research skill set recommended by a World Health Organization training manual and required the successful defense of a health systems-focused research paper. Students had 324 hours of research capacity-related subjects utilizing lectures, exercises, small group discussions, mentoring, and mock defenses. There were successful grant applications and research partnerships established with the Department of Health, among others. The program produced 88 papers, one was published and 5 were presented in local and international conferences. Policymakers and program implementers were members of the thesis defense panel. Students were recognized as research leaders in medical school. Few teams kept in contact with their collaborators. Research infrastructure was manifest in research implementation plans containing objectives, Gantt charts, and budgets. Conclusion: A university-based health research capacity-building program has been successful in building skills and confidence in developing partnerships, and investing in research infrastructure. It needs to strengthen strategies for research dissemination and impact and for building elements of continuity and sustainability.